Strategic management and business policy : globalization, innovation, and sustainability - Wheelen, Thomas L. (Harlow, UK : Pearson, 2018)
Picking up where the popular previous editions left off, Strategic Management and Business Policy: Globalization, Innovation and Sustainability, 15th Edition further sharpens and modernizes this classic text's approach to teaching strategy with an emphasis on globalization, innovation, and sustainability. Throughout, the authors equip students with the strategic concepts they will need to know as they face the issues that all organizations must build upon to push their businesses forward. In this edition, Alan Hoffman and Chuck Bamford bring a fresh perspective to this extraordinarily well -researched and practically crafted lesson. Also included is a new chapter on Global Strategy, along with new vignettes and comprehensive, real-world case studies.
Part One: Introduction to strategic management and business policy -- Part Two: Scanning the environment -- Part Three: Strategy formulation -- Part Four: Strategy implementation and control -- Part Five: Introduction to case analysis -- Part Six: Cases in strategic management.
Includes bibliographical references and index.
Keywords: Strategic planning -- Case studies; Strategic planning